Research on Bonding Performance of Anchorage Caisson Foundation with Different Contact Surfaces and Grouting Bed - Tiesuo Geng; Shuanghua Chen; Liuqun Zhao; Zhe Zhang (Buildings, 2021)
In view of the first domestic offshore suspension bridge with caisson foundation, this paper mainly studies the bonding properties between underwater pre-filled aggregate grouting bed and anchorage caisson foundation. Through the test, the cohesive force of adding ordinary concrete between the anchorage caisson foundation and the grouting bed, the cohesive force of adding paper base asphalt felt between the anchorage caisson foundation and the grouting bed, and the cohesive force of adding geotextile between the anchorage caisson foundation and the grouting bed are measured, respectively. When the contact surface is concrete and geotextile, the fracture form of the specimen was analyzed by numerical simulation, and the AE variation trend of the two specimens have been studied. The results of this article can provide references for other projects.